The happiness turn? Mapping the Emergence of “Happiness Studies” Using Cited References. - Kullenberg, Christopher; Nelhans, Gustaf (University of Gothenburg, 2015)
The study analyzes “happiness studies” as an emerging field of inquiry throughout various scientific disciplines and research areas. Utilizing four operationalized search terms in the Web of Science; “happiness”, “subjective well-being”, “life satisfaction” and “positive affect”, a dataset was created for empirical citation analysis. Combined with qualitative interpretations of the publications, the results show how happiness studies have developed over time, in what journals the citing papers have been published, and which authors and researchers are the most productive within this set. The conclusion is that “happiness studies” have emerged in many different disciplinary contexts and progressively been integrated and standardized. Moreover, beginning at the turn of the millennium, happiness studies have even begun to shape an autonomous field of inquiry, in which happiness becomes a key research problem for itself, and we may even speak of a “happiness turn”.

Purpose:

The study aims at drawing a more precise map of the scientific research contexts in which happiness studies have become a core activity, an integrated part of research, or a peripheral side-activity to normal science within a pre-existing discipline. The aim is to show how a new research field - ‘‘happiness studies’’ - has emerged, consolidated and become integrated into practices of research.

I studien analyseras lyckoforskning (happiness studies) som ett framväxande forskningsfält inom olika vetenskapliga discipliner och forskningsområden. Genom att använda fyra operationaliserade söktermer i Web of Science: “happiness”, “subjective well-being”, “life satisfaction” och “positive affect” har en datamängd för empirisk citeringsanalys skapats. I kombination med kvalitativa tolkningar av publikationerna, visar resultaten hur lyckoforskning har utvecklats över tid, i vilka tidskrifter artiklar som citeras har publicerats och vilka författare och forskare som har varit mest produktiva inom området. Slutsatsen är att lyckoforskning har vuxit fram i ett antal olika disciplinära sammanhang och har successivt integrerats och standardiserats. Dessutom började vid millennieskiftet lyckoforskning att forma ett självständigt forskningsfält, där lycka (happiness) blir ett viktigt forskningsproblem i sig självt. Detta kan man kalla för “happiness turn”.

Syfte:

Studien syftar till att förklara de vetenskapliga forskningssammanhang där lyckoforskning ("happiness studies") har blivit en kärnverksamhet, en integrerad del av forskningen, eller en sidoaktivitet till vanlig vetenskap inom en redan existerande disciplin. Syftet är att visa hur ett nytt forskningsfält "Happiness studies" har vuxit fram, konsoliderats och integrerats i forskningen.
The happiness turn? Mapping the Emergence of “Happiness Studies” Using Cited References.
Keywords: theory of science; vetenskapsteori; happiness studies; lyckoforskning; bibliographic coupling; bibliografisk koppling; multidisciplinary; tvärvetenskaplig; cited references; citerade källor; scientometrics; scientometri; bibliometrics; bibliometri; citation analysis; citeringsanalys; Philosophy; Filosofi; Other Humanities not elsewhere specified; Övrig annan humaniora; History of Science and Ideas; Idé- och lärdomshistoria